Dopamine sensor in real sample based on thermal plasma silicon carbide nanopowders. (August 2019) - Sarno, Maria; Galvagno, Sergio; Scudieri, Carmela; Iovane, Pierpaolo; Portofino, Sabrina; Borriello, Carmela; Cirillo, Claudia
Abstract: Silicon carbide nanopowders(SiC_PL) were prepared via thermal plasma synthesis. The electrocatalytic activity of the SiC_PL coatedglassy carbon electrode ( GCE) towards the electrochemical oxidation ofdopamine ( DA), ascorbic acid ( AA), anduric acid ( UA), was characterized bycyclic voltammetry ( CV), in 0.1 M phosphate buffer solution(PBS) at pH7 . The peaks of oxidation for DA, AA, and UA result well separated on the modified electrode in contrast with the behavior shown on bare GCE. A lowlimit of detection ( LOD) of 0.043 μM was found at the SiC_PL coated GCE. In a real sample, the recovery rates of the added compound were98.8%, 106.5% and 100.7%, indicating a potential for the SiC_PL electrode to determine DA in real conditions. The results of the characterization as supercapacitor electrodeshow that the specific capacitance for SiC_PLis of 151.2 F/g at 0.12 A/g. After 2.5 × 10 5 cycles SiC electrode still retains about 90% of its initial capacitance showing good stability. Highlights: SiC nanopowders obtained by thermal plasma in a pre-pilot plant. Dopamine sensor in a real sample. High specific capacitance and good rate capability. Electrochemical stability.